The Haitian threat: humanitarianism, security, and internally displaced Haitians following the 2010 earthquake - Yeargain, Kelsy (AUC Knowledge Fountain, 2011)
This thesis explores the relationships between internally displaced Haitians, humanitarian organizations, and the international community. The thesis focuses primarily on humanitarianism as a mechanism of security and the framing of displaced Haitians as security threats. I engaged with the discourses of the media and humanitarian organizations, as well as interviews conducted with aid workers in Haiti following the earthquake. Exploring the dynamic relationships of humanitarian organizations, the international community, the Haitian government and the internally displaced Haitians, this thesis attempts to problematize the many assumptions about international humanitarian aid and the Haitian population. There are three major focuses of the thesis: the increasing use of security in the distribution of humanitarian aid, humanitarianism operating as a mechanism of security and the construction of meaning and threat. By complicating humanitarian assistance as not just an act of goodwill towards mankind and by arguing that the failures of delivering humanitarian aid post- earthquake were not the result of inefficiencies, violent Haitians or a corrupt â failed state.â They are instead the result of humanitarianism functioning as a mechanism of governance, the prioritization of security in the distribution of aid, and how Haitians and the Haitian state are discursively represented as both hopeless and caught in a vicious cycle of poverty and violence, and as potential security threats to themselves, to Haitian women and to aid workers. This thesis discusses the very foundation of humanitarianism itself and the relationship between humanitarianism as an industry, the international system, security, representational practices and the construction of threats and ask how these multiple issues intersect to create the kind of humanitarianism that we see in post-earthquake Haiti. This thesis explores how the dominant narratives about humanitarianism and Haitians are a reflection of the unequal power distribution of the international community and how those narratives construct to portray Haitians and internally displaced populations in a particular way to help justify political interventions, which in turn recreate and reconstruct the meanings and identities of the population. Deconstructing dominant narratives about humanitarianism allows for a more nuanced exploration of what exactly humanitarianism is and how it functions as a mechanism of power, governance and security.